Diatom Frustule‐Inspired Metamaterial Absorbers: The Effect of Hierarchical Pattern Arrays. (28th February 2019) - Li, Aobo; Zhao, Xiaoguang; Duan, Guangwu; Anderson, Stephan; Zhang, Xin
Abstract: Diatoms are photosynthetic algae that exist ubiquitously throughout the planet in water environments. Over the preceding decades, the diatom exoskeletons, termed frustules, featuring abundant micro‐ and nanopores, have served as the source material and inspiration for myriad research efforts. In this work, it is demonstrated that frustule‐inspired hierarchical nanostructure designs may be utilized in the fabrication of metamaterial absorbers, thereby realizing a broadband infrared (IR) absorber with excellent performance in terms of absorption. In an effort to investigate the origin of this absorption characteristic, numerical models are developed to study these structures, revealing that the hierarchical organization of the constituent nanoparticulate metamaterial unit cells introduce an additional resonance mode to the device, broadening the absorption spectrum. It is further demonstrated that the resonant peaks shift linearly as a function of inter‐unit‐cell spacing in the metamaterial, which is attributed to the induced collective dipole mode by the nanoparticles. Ultimately, the work herein represents an innovative perspective in terms of the design and fabrication of IR absorbers inspired by naturally occurring biomaterials, offering the potential to lead to advances in metamaterial absorber technology. Abstract : A hierarchical hexagonal design of nano resonators is used to realize a near‐infrared metamaterial absorber, inspired by the hierarchical design of diatom frustule pores. With an additional degree of freedom (hierarchy) in the design of metamaterial resonators, a widened high‐absorption band in the spectrum has been demonstrated by the measurements from experiments and from numerical and analytical calculations.